2021
DOI: 10.1007/s12650-021-00797-5
|View full text |Cite
|
Sign up to set email alerts
|

Numerical visualization of drop and opening process for parachute-payload system adopting fluid–solid coupling simulation

Abstract: In order to study the fluid–solid coupling dynamic characteristics of parachute-payload system during drop process and analyze the unsteady aerodynamic characteristics under finite mass opening conditions, an adaptive moving fluid mesh method is developed on the basis of the existing arbitrary Lagrangian–Eulerian (ALE) fluid–solid coupling method. The calculation results of open force and drop velocity on the C-9 parachute demonstrate the effectiveness of this method. On this basis, the effect of canopies with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…Parachute recovery has a wide range of applications [23]. The mass of what is recovered ranges from a few kilograms to dozens of tons; the opening speed ranges from low to supersonic; and the height spans from thousands of meters to dozens of kilometers, which can safely and effectively slow the recovered UAVs down to the ground or water surface.…”
Section: Overview Of Parachute Ejecting Tractor Rocketmentioning
confidence: 99%
“…Parachute recovery has a wide range of applications [23]. The mass of what is recovered ranges from a few kilograms to dozens of tons; the opening speed ranges from low to supersonic; and the height spans from thousands of meters to dozens of kilometers, which can safely and effectively slow the recovered UAVs down to the ground or water surface.…”
Section: Overview Of Parachute Ejecting Tractor Rocketmentioning
confidence: 99%
“…Cao et al [14] conducted aerodynamic simulations for the inflation of a blunt-body canopy without opening, and demonstrated that ALE, DSD/SST and IB methods have outstanding advantages in dealing with free surface flow problems. Chen et al [15] used the fluid-solid coupling method to conduct aerodynamic simulation analysis of the opening and steady descent processes during the landing of the parachute-load system, using a simple round parachute with an canopy without opening still. Most of the recent studies on the aerodynamics of the parachute on board the return module only MMEAT-2022 Journal of Physics: Conference Series 2383 (2022) 012078 build simple seamless parachute models as the research subjects, which differs greatly from the actual canopy configuration.…”
Section: Introductionmentioning
confidence: 99%